The PRO‐HOME Project. A multicomponent intervention for the protected discharge from the hospital of multimorbid and polytreated older individuals by using innovative technologies: A pilot study - Alberto Pilotto; Erica Volta; Marina Barbagelata; Alessandra Argusti; Antonio Camurri; Niccolò Casiddu; Carlo Berutti‐Bergotto; Carlo Custodero; Alberto Cella (Wiley, 2024)
Abstract Backgroud Discharge planning from the hospital of frail older patients is an important step to avoid inappropriate long‐stay hospitalizations and to prevent the risks related to the prolonged hospitalization. In this frame, we developed an experimental trial-'PRO‐HOME', a multicomponent programme of interventions for multimorbid and polytreated hospitalized older patients. Aim The main aim of the study was to develop a protected discharge facility using a mini apartment equipped with advanced architectural and technological components to reduce the length of hospital stay of older participants (aged 65+ years old) admitted to the hospital for an acute event, deemed stable and dischargeable. Materials and Methods This is a pilot randomized controlled study, comparing 30 hospitalized participants included in a multidimensional, transitional care programme based on information and communication technologies to 30 patients in standard usual care until hospital discharge. Results We presented the study design of the PRO‐HOME programme, including architectural and technological components, the enrolment procedures, the components of the intervention that is physical activity, cognitive training and life‐style education and the evaluation method of the intervention based on the Comprehensive Geriatric Assessment to explore the changes in the individual domains that are target of the multicomponent intervention. Conclusions The final results will suggest whether the PRO‐HOME programme represents a useful and feasible intervention to reduce the length of hospital stay of multimorbid and polytreated hospitalized older patients and improve their physical and cognitive performances and overall quality of life. Patient or Public Contribution Due to the characteristics of the population of interest of the PRO‐HOME study, we involved in the study design and programme of the activities the participants enrolled in a previous smart home‐based project named MoDiPro carried‐out during a 3‐year period. The elderly participants from the local population involved were asked, by means of focus groups, for feedback on their experience in MoDiPro, and their suggestions were integrated into the design phase of the current PRO‐HOME project. The focus groups included open group interviews with a qualitative collection of the patients' feedback so that the participants could interact with each other.